Ответ:
3
Объяснение:
F(3)
1) F(n) = F(3) (n=3)
n = 3 > 2 → да
F = F(2)+F(1) =...
______________
2) F(n) = F(2) (n=2)
n = 2 > 2 → нет
F = n = 2
3) F(n) = F(1) (n=1)
n = 1 > 2 → нет
F = n = 1
→
... = F(2)+F(1) = 2+1 = 3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
3
Объяснение:
F(3)
1) F(n) = F(3) (n=3)
n = 3 > 2 → да
F = F(2)+F(1) =...
______________
2) F(n) = F(2) (n=2)
n = 2 > 2 → нет
F = n = 2
3) F(n) = F(1) (n=1)
n = 1 > 2 → нет
F = n = 1
______________
→
... = F(2)+F(1) = 2+1 = 3